PENGARUH SIKAP FINANSIAL DAN PERILAKU FINANSIAL TERHADAP TARAF LITERASI FINANSIAL MAHASISWA - Renata Pratiwi; Fahimul Amri (FKIP Unswagati, 2022)
AbstractÂ The research aims to explain the effect of financial atitude on the level of financial literacy, explain the effect of financial behaviour on the level of financial literacy, and explain the influence of financial atitude and financial behaviour on the level of financial literacy. This research is a type of quantitative descriptive research. The population in this study were students of STKIP PGRI Jombang class 2018-2021. The sampling technique used proportional random sampling technique, in order to obtained the number of respondens as much as 311 people. The research instrumen used a questionaire. The data analysis technique used descriptive analysis and multiple linear regression analysis. The results showed that the level of financial literacy of STKIP PGRI Jombang students in the 2018-2021 batch was 4.01 which was in the high category. In addition, this study is able to prove that financial atitude affects the level of student financial literacy, financial behaviour affects the level of student financial literacy, and financial atitude and financial behaviour affect the level of student financial literacy.Keywords: finanncial literacy, financial atitude, financial behaviour